Exploitation and Resilience: The Singosari Community Faces Environmental Threats - Rico Tomboti; Khoiron Khoiron; Langgeng Rachmatullah Putra (Publica: Jurnal Pemikiran Administrasi Negara, 2026)
This study examines the dynamics of Singosari residents' resistance to the Singhasari Special Economic Zone (SEZ) project, focusing on the discursive mechanisms that construct meanings of exploitation, local identity, and ecological injustice. The researcher used Van Dijk's theory-based Critical Discourse Analysis (CDA) that integrates text triangulation, social cognition, and context. The primary data consisted of protest banners from residents and narratives from community leaders, including Ki Ardhi Purbo Antono and Fatkul Ulum (Gus Ulum), while supporting data were obtained from international literature on environmental injustice and the failure of the Environmental Impact Assessment (EIA). The results show that the narrative "SEZ = Capitalism Exploiting the Area" and the Javanese-language banners and the identity of Islamic boarding school students (santri) function as tools for deconstructing the discourse of state development. The discursive mechanisms were identified through the construction of binary oppositions (business district vs. Islamic boarding school, people vs. capital), the framing of structural injustice and environmental injustice, and the formation of collective consciousness through critical cognition of policy. These findings confirm that CDA effectively exposes the structural injustices hidden within the discourse of "rapid economic growth" and emphasizes the need for inclusive, participatory development that is oriented toward environmental sustainability and social justice.